2001
DOI: 10.1177/03635465010290020401
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Comparison of Posterior Cruciate Ligament Reconstruction Techniques

Abstract: Most posterior cruciate ligament reconstruction techniques use both tibial and femoral bone tunnels for graft placement. Because of the acute angle the graft must make to gain entrance into the tibial tunnel, abnormal stresses are placed on the graft that could lead to graft failure. An alternative technique for posterior cruciate ligament reconstruction involves placement of the bone plug from the graft anatomically on the back of the tibia (inlay), preventing formation of an acute angle at the tibial attachm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
163
2
11

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(183 citation statements)
references
References 31 publications
7
163
2
11
Order By: Relevance
“…This technique was called into question given the ''killer turn'' imposed on the PCL graft at the aperture of tibial tunnel. The killer turn was associated with friction, graft stretch, and fatigue failure [4,[31][32][33]56]. Although some clinical studies have not found a difference between the transtibial and open inlay techniques [2,29], there is also a body of literature to suggest unsatisfactory results with residual laxity given the transtibial technique [10,21,25,53].…”
Section: Introductionmentioning
confidence: 99%
“…This technique was called into question given the ''killer turn'' imposed on the PCL graft at the aperture of tibial tunnel. The killer turn was associated with friction, graft stretch, and fatigue failure [4,[31][32][33]56]. Although some clinical studies have not found a difference between the transtibial and open inlay techniques [2,29], there is also a body of literature to suggest unsatisfactory results with residual laxity given the transtibial technique [10,21,25,53].…”
Section: Introductionmentioning
confidence: 99%
“…These PCL reconstruction techniques (single graft and double graft reconstructions) have been compared in previous experimental studies (Bergfeld et al, 2001;Hagemeister et al, 2002;Mannor et al, 2000;Race and Amis, 1996;Race and Amis, 1998;Stahelin et al, 2001). Harner et al (2000b) have shown that the kinematics behavior of a knee with a ''native'' PCL and a knee with double graft reconstructed PCL were similar.…”
Section: Introductionmentioning
confidence: 99%
“…The early biomechanical studies opposing PCL transtibial and inlay techniques have shown that the inlay technique was superior in restoring the posterior stability after PCL reconstruction [1,12]. While these differences were observed in a cadaveric model, these results did not ultimately translate into superior clinical outcomes.…”
mentioning
confidence: 96%